Saccidānanda-bigraha Śrīśrīmā Ānandamaẏī - Rāẏa, Kāmākhyā Prasāda (Kā.Pra. Rāẏa ; prāptisthāna Nātha Brādārsa, 1979)
On the life of the female Bengali Hindu religious leader Ānandamaẏī, b. 1896; includes songs in praise of Ānandamaẏī